A phase II trial of hypofractionated high-dose proton beam therapy for unresectable liver metastases. (November 2022) - Kim, Kangpyo; Yu, Jeong Il; Park, Hee Chul; Yoo, Gyu Sang; Lim, Do Hoon; Noh, Jae Myoung; Jeong, Woo Kyoung
Highlights: The first phase II study using BED > 100 GyE with PBT in treatment of liver metastases. 6-month FFLP was 95.2% of without grade ≥3 treatment-related toxicities. Size of the metastasis and use of systemic agents were associated with the FFLP rate. KRAS and TP53 mutations in colorectal cancer subgroup were not prognostic. Abstract: Background and purpose: Proton beam therapy (PBT) is an effective treatment option for primary malignant liver disease. However, evidence regarding liver metastasis is insufficient. We aimed to investigate the efficacy and safety of hypofractionated high-dose PBT in the treatment of metastatic liver disease. Materials and methods: From January 2019 to January 2021, patients with unresectable liver metastases were enrolled. For PBT, the dose schemes of 60 Gy relative biological effectiveness (GyRBE) in 5 fractions (fx) (biologically effective dose [BED] 132 GyE) or 70 GyRBE in 10 fx (BED 119 GyE) were used. Either a passive scattered beam or pencil beam scanning (PBS)-based intensity-modulated proton therapy (IMPT) was performed with proper respiratory management. The primary endpoint of the study was 6-month freedom from local progression (FFLP) rate; and the Kaplan–Meier method was used to calculate the FFLP and survival rates. Results: Of the 49 liver metastases in 46 patients, the colorectum accounted for 60% of the primary cancer sites, followed by the gastrointestinal organs and pancreas/biliary tract. Forty patients presented only 1 liver metastasis, while the other 6 patients had 2 to 4 metastases. The Six-month FFLP rate was 95.2%. The 1-year FFLP rate in patients with <3 cm liver metastasis was 87.4%, while that was 74.1% in patients with > 3 cm group (p = 0.087). With regard to systemic treatment, the 1-year FFLP rate after PBT was better (94.1%) than that without systemic treatment (75.8%; p = 0.051). Regarding PBT-related toxicity, one patient developed a grade 2 gastric ulcer, while none of the patients developed grade ≥3 toxicities. Conclusions: Hypofractionated PBT with a BED > 100 GyRBE for liver metastasis is safe and effective, given the high rate of 6-month FFLP without grade ≥3 treatment-related toxicities. However, further improvements are required for larger tumors and/or those without prior systemic therapy.